Ruins of sub-shrines - Temples of India Project Team (Jio Institute, 2024)
Around a dozen of subsidiary shrines were built on Harsha Hill in the 10th and 11th centuries. These were dedicated to various Brahmanical deities, as evidenced by architectural fragments. Unlike a Panchayatan temple or a planned temple complex, the irregular placement and size proportions of these sub-shrines suggest a randomness and unplanned construction over an extended period. They exhibit a variety of pitha usually corresponding to the Maha-Maru styles, but some of them also exhibit Maha-Gurjara features.